The application of the dimensions of TQM and its impact in enhancing the satisfaction of the taxpayers: Applied Study in the General Commission for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The concept of TQM is based on one of the concepts that combine administrative and innovative methods. The aim of the research is to demonstrate the dimensions of TQM in enhancing the satisfaction of the taxpayers through a survey of a sample of officials in the General Authority for Taxation and 50 officials. In the collection of data and information, and the results were analyzed using the SPSS program to find the most important compounds and factors in he method of analysis.